Diagnostic Dilemma of a Rare, Giant Retroperitoneal Schwannoma: A Case Report and Review of Literature - Mahendra Singh; Lovekesh Kumar; Rajkumar Chejara; Om Prakash Prasad; Yuvraj Kolhe; Ashish Saxena (Case Reports in Oncological Medicine)
Schwannoma is a benign tumour of peripheral nerve sheath. It usually arises from head, neck, and trunk. Retroperitoneal schwannoma is a rare entity, accounting for only 0.3–3% of total schwannomas. Majority of retroperitoneal schwannomas reported in literature have a diameter of 5 to 15 cm. Preoperative diagnosis is difficult due to low frequency, nonspecific clinical course, and nonspecific imaging features. Histology usually provides definitive diagnosis. Schwannomas are solitary, well-circumscribed, and noninvasive, so complete surgical excision provides good result. We report a case of a 23-year-old male, who presented with progressive abdominal distension and intermittent episodes of intestinal obstruction. CECT was suggestive of huge solid-cystic mass in abdominopelvic region. Image guided percutaneous aspiration revealed around 1 litre of frank pus and FNAC was suggestive of abscess. Exploratory laparotomy revealed a large 32 × 28 × 26 cm mass with solid and cystic components containing 1 litre of pus. Histological features of tumour were suggestive of benign schwannoma and immunohistochemistry for S-100 was positive. Postoperative recovery was uneventful. We report this case of a retroperitoneal schwannoma because of giant size, rare location, unusual presentation, and diagnostic dilemma.